Can dissociative amnesia be a residual symptom of prolonged complex post-traumatic stress disorder? - İzzet Çağrı Metin; Selman Yıldırım; Aykut Karahan (Annals of General Psychiatry)
Abstract Background Dissociative amnesia, a disorder characterized by impairments in multiple memory areas, is frequently associated with trauma. Complex post-traumatic stress disorder (CPTSD) is marked by mood dysregulation, negative self-concept, and impaired interpersonal relationships, in addition to the classic symptoms of post-traumatic stress disorder (PTSD). The relationship between CPTSD and dissociative amnesia, as well as whether CPTSD should be considered a dissociative subtype, remains uncertain in the literature. Individuals diagnosed with CPTSD tend to exhibit higher levels of dissociative symptoms than those diagnosed with PTSD. Clinical presentation We present the clinical report of a 42-year-old male who, after a car accident, exhibited core symptoms of PTSD along with symptoms of self-organization disorders. While these symptoms persisted, the patient developed dissociative amnesia years after the trauma. Neuroimaging studies, psychometric tests, reviewed hospital records, and clinical interviews were conducted to speculate on the differential diagnosis of organic psychiatric conditions and potential diagnoses. The possible relationship between dissociative amnesia and complex post-traumatic stress disorder was examined. Conclusion This case demonstrates the complexity of differentiating dissociative amnesia from organic conditions. Discussing the possible shared mechanisms between CPTSD and dissociative amnesia could contribute to a better understanding of both conditions.